EFFECTIVENESS OF SIMP KS3B APPLICATION IN IMPROVING FAMILY PLANNING SERVICE QUALITY - Lusi Herlina; Ma'mum Sutisna; M Alam Syah Aziz; Herri S Sastramihardja; Leri Septiani; Hidayat Wijayanegara (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Injectable contraception is a hormonal contraceptive method administered through injection and consists of two types, namely DMPA (Depo Medroxy Progesterone Acetate) and combination. Monitoring and management of data on participants in the 3-month injectable contraception program is carried out through the SIMP KS3B application so that health workers can provide more targeted services. This study aims to assess the effectiveness of using the SIMP KS3B application in improving the quality of family planning services in the working area of the Denkesyah Garut Clinic. The research method used a quasi-experimental design with a posttest nonequivalent control group. The research population consisted of midwives in the working area of the Denkesyah Clinic, with purposive sampling technique. Univariate data analysis used frequency distribution, while bivariate analysis used the Mann Whitney test and multivariate analysis used logistic regression. The study was conducted from December 30, 2024, to January 17, 2025. The results showed that the dimensions of ease, usefulness, interest, and actual use had a value of ρ = 0.000. Multivariate analysis showed that the dimension of actual use was the most influential with a beta coefficient value of 2.310 (ρ = 0.000). In conclusion, the SIMP KS3B application is more effective than manual family planning records in improving the quality of family planning services. It is recommended that this application be recommended by the Health Office as a medium for recording and reporting family planning services.